Potential energy savings by radiative cooling system for a building in tropical climate - Hanif M.; Mahlia T.M.I.; Zare A.; Saksahdan T.J.; Metselaar H.S.C. (2023)
Nowadays, almost every building required a cooling system and most of them use active cooling, which normally operates using electricity generated from non-renewable fossil fuel. To achieve comfort, it is possible to utilize the natural environmental conditions to partially replace the active cooling energy requirements. This research attempts to investigate the correlation between the radiative cooling power and the temperature difference between the ambient and the sky. The potential of a radiative cooling system in Malaysia is evaluated as well. The radiative cooling system operates by using a flat-plate rooftop as a radiator to reject heat to the cooler nocturnal sky for cooling purposes. In addition, the radiative cooling potential is determined by using the climate data of 10 different locations in Malaysia. The study found that radiative cooling can save up to 11% of the power consumption for cooling purposes. This value is the same for all 10 locations in this country. © 2014 Elsevier Ltd.